Approach to refractory gastroesophageal reflux disease - Zuluaga Arbeláez, Nicolás (2024)
An adequate approach to refractory gastroesophageal reflux disease (rGERD) for achieving therapeutic success. From the precise definition of rGERD to the characterization of its phenotypes, it will pave the way for the customization of therapy for each patient. In this narrative literature review, the aim is to provide an synthesis of the utility of various diagnostic tools and explore the wide options, both medical and invasive, available for this condition.